Wonder bra, starbucks, fireflies and other images in Genevieve L. Asenjo's poetry - Deriada-Manaog, Dulce Maria V. (Danyag :the UPV journal of humanities and social sciences)
"This paper looks into the three motifs identified in the poems of Genevieve L. Asenjo: woman as an empowered individual who celebrates her body and her sexuality, big city life and living, and an individual's attachment to one's origins. These motifs are discussed in relation to feminist ideas, modernity and local diaspora, and nostalgia. The poems under the first motif show how women resist and challenge patriarchy. Moreover, Asenjo's women poems disclose how women celebrate their bodies through writing thus reclaiming these as primarily theirs before anyone else's. The poems under the second motif reveal how local diaspora has not made life any better for rural dwellers who migrate to the big city in the hope of having much better life. Likewise, Asenjo's big city life and living poems affirm how technology has significantly impacted the lives of city dwellers. Despite an individual's migration to the big city, one is still attached to one's roots as seen in the poems under the third motif. Consequently, nostalgia is used as a form of hope and escape for the once rural dweller who is trapped in the rigorous and harried city life."